2015
DOI: 10.1007/s10792-015-0110-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and distribution of paravascular lamellar holes and their relationship with macular retinoschisis in highly myopic eyes using spectral-domain oct

Abstract: The purpose of the study is to determine the incidence and distribution of paravascular lamellar holes (PLH) around retinal vessels in highly myopic eyes and their relationship with macular retinoschisis (MR). We examined 306 eyes of 178 patients with high myopia, performing multiple scans of the posterior pole within the retinal vascular arcades using spectral-domain OCT. Type of staphyloma was determined. PLH were divided into three groups: holes only (group 1), holes extending below vessels (group 2), and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Vela et al. () recently reported a higher incidence of paravascular lamellar holes along the inferior temporal vascular arcades and suggested that this result may relate to the type of staphyloma with evidence indicating an inferior shift of staphyloma apex (Ikuno & Tano ; Ohno‐Matsui ). We considered the difference may result from the much higher prevalence of wide macular staphyloma in our study.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Vela et al. () recently reported a higher incidence of paravascular lamellar holes along the inferior temporal vascular arcades and suggested that this result may relate to the type of staphyloma with evidence indicating an inferior shift of staphyloma apex (Ikuno & Tano ; Ohno‐Matsui ). We considered the difference may result from the much higher prevalence of wide macular staphyloma in our study.…”
Section: Discussionmentioning
confidence: 98%
“…; Vela et al. ). The pathogenesis of lamellar holes detected adjacent to retinal vessels remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations